Development of the Erdanela model for stroke prevention in the elderly: Effectiveness Test - Erdanela Setiawati; Nur Indrawaty Lipoeto; Yuliarni Syafrita; Adang Bachtiar (Jurnal Penelitian Pendidikan IPA, 2022)
A new stroke-prevention service (ERDANELA model) has been developed at nursing homes by empowering elderly caregivers to become service-implementing cadres. The aim of this study is to investigate the effect of empowerment on the knowledge, attitude, skill, and behavior of elderly caregivers about stroke-prevention services in nursing homes. A quasi-experimental study was conducted on 52 elderly caregivers who were working at 3 nursing homes in West Sumatra Province, Indonesia. The questionnaire design consists of knowledge, attitudes, skills, and behavior variables. Intervention in the form of training was carried out for three days, using pre-test and post-test methods. The results of this research are the majority of caregivers are 40-49 years old (34.60%), male (51.9%), have middle school education (48.10%), have monthly income bigger than the RMW (75.00%), worked in nursing home>5 years (67.30%), and never attended training while working at nursing-home (73,10%). Caregivers knowledge, attitude, skill, and behavior mean was 18.23±1.89, 7.65±1.22, 6.75±1.37 and 6.00±0,91 respectively before training, and significantly it has increased to 25.48±3.38, 10.15±.09, 9.10±0.96, and 7.06±1.43 respectively after training with sig=0.000<0.05. Empowerment has succeeded in increasing the knowledge, attitudes, skills, and behaviors of elderly caregivers to become service-implementing cadres of the new stroke-prevention service at nursing homes